Aglomeração urbana descontínua de Montes Claros/MG: novas configurações socioespaciais - França, Iara Soares de (2012)
The process of expansion of the cities involves their growth and the growth of its surrounding areas presenting, or not, continuity in the occupation. This demonstrates that the political and administrative criteria lead to formation of areas of economic and population concentration. The interrelationships developed between cities of the same region impact the territory organization, whereas the core city draws population, investments, flow of goods, circulation, transportation and estate so that its attraction radius extrapolates the territory political and administrative boundaries. The intensification of urbanization is a relevant aspect in this analysis since it reaches surrounding areas making the city spatially dispersed with population concentration and economic activities. This study analyzed the discontinuous urban agglomeration of Montes Claros/MG and its surrounding municipalities. It is observed, in the North of Minas Gerais, spatial and socioeconomic integration, and not political/administrative between the medium city of Montes Claros and its surrounding municipalities. These interactions were identified from the intense commute among those cities in search of health services, higher education, specialized and diversified trade, and workplace. This research was structured in three steps: the first one was research and literature review. Documentary research was carried out after delimitation of study area. The third step of the research was based on use of primary sources: field research in the area of study and structured interviews applied to public managers, business entrepreneurs, taxi drivers and population of the municipalities. Afterwards, the secondary information was added to the content of primary sources for writing and presentation of outcomes of this study regarding the process of urban agglomeration in medium cities.